The Influence of Leadership and Organizational Culture on Employee Performance with Work Discipline As A Mediating Variable At The Health Office Of Bengkalis Regency, Riau Province (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to find out and analyze the influence of leadership and organizational culture on employee discipline and performance. To find out and analyze the influence of discipline on employee performance. To find out and analyze the influence of leadership and organizational culture on employee performance through employee discipline of the Bengkalis Regency Health Office, Riau Province. The population referred to in this study is all employees who work at the Bengkalis Regency Health Office which amounted to 146 people, the number of samples used was 107 people. The research method used is quantitative. The data analysis used in this study is Structural Equation Modelling (SEM). The findings of the study show that a) leadership has a coefficient value of 0.631, with t statistic 4.968 and p value 0.000. b) Organizational culture has a coefficient value of 0.241, with a t statistic of 3.849 and a p value of 0.000. c) Work Discipline has a coefficient value of 0.203, with t statistic 3.269 and p value 0.000. d) Organizational culture has a path value of 0.218 coefficient value, with t statistic 3.957 and p value 0.000. e) Leadership has a path coefficient value of 0.336, with a T statistic of 3.204 and a P value of 0.000. f) Leadership has a coefficient value of 0.272, with a t statistic of 2.338 and a p value of 0.020.g) Organizational culture has a coefficient value of 0.276, then a statistical t value of 2.484 and a p value of 0.017. Conclusion a) leadership affects work discipline. b) Organizational culture affects work discipline. c) leadership affects employee performance. d) Organizational culture affects employee performance. e) Work discipline has a significant effect on employee performance. f) leadership has a significant effect on employee performance through work discipline. g) Organizational culture has a significant effect on employee performance through work discipline.